(untitled) (LEARNing Landscapes, 2009)
Literacy definitions, the growth of inquiry literacy in science education, and the developmental nature of inquiry literacy within learners’ experiences in diverse content domains are outlined. Classroom-based vignettes illustrate elements of inquiry literacy in science, social studies, and mathematics. A preliminary list of qualities of student inquiry literacy is presented. These qualities could potentially be monitored in individuals and classrooms as the range of literacy knowledge, skills, and dispositions increases in breadth, depth, and fluency.